Radiation hardness and lifetime studies of LEDs and VCSELs for the optical readout of the ATLAS SCT - Beringer, J; Borer, K; Mommsen, R; Nickerson, R; Weidberg, A; Monnier, E; Hou, H; Lear, K (Elsevier, 1999)
We study the radiation hardness and the lifetime of Light Emitting Diodes (LEDs) and Vertical Cavity Surface Emitting Laser diodes (VCSELs) in the context of the development of the optical readout for the ATLAS SemiConductor Tracker (SCT) at LHC. About 170 LEDs from two different manufacturers and about 130 VCSELs were irradiated with neutron and proton fluences equivalent to (and in some cases more than twice as high as) the combined neutral and charged particle fluence of about 5×1014 n (1 MeV eq. in GaAs)/cm2 expected in the ATLAS inner detector. We report on the radiation damage and the conditions required for its partial annealing under forward bias, we calculate radiation damage constants, and we present post-irradiation failure rates for LEDs and VCSELs. The lifetime after irradiation was investigated by operating the diodes at an elevated temperature of 50 °C for several months, resulting in operating times corresponding to up to 70 years of operation in the ATLAS SCT. From our results we estimate the signal-to-noise ratio and the failure rate of optical links using LEDs developed specifically for application at LHC.